Cuidados orais e o uso de flúor na prevenção da cárie relacionada à radiação – uma revisão de escopo - Carvalho, Allyne Jorcelino Daloia de (2022)
Radiotherapy in the head and neck region can cause adverse effects to the oral cavity of patients. Radiation-related caries is a serious complication of radiation and presents difficult prevention and treatment, negatively impacting the patient’s quality of life. The aim of this scoping review was to map the literature about oral hygiene protocols and the use of fluoride in patients who received radiotherapy. For this, the PRISMA-P protocol was followed and the review was registered in the Open Science Framework (OSF). The review was reported according to the PRISMA SrC list of recommendations and following the recommendations of the JBI Evidence Synthesis Manual for Scope Reviews. MEDLINE (PubMed), SciELO, Scopus, EMBASE (Ovid), Web of Science, LILACS, LIVIVO and Cochrane Library were primary sources. Part of the “gray literature” was searched in EASY and ProQuest databases. Studies that used radiotherapy in the head and neck region and that evaluated the occurrence of radiation-related caries were included. There were no restrictions of study language or publication date. Thus, clinical trials (randomized or not) and observational studies (prospective and retrospective) were included. Two eligibility reviewers participated in study selection and data analysis. The qualitative synthesis was performed in a narrative/descriptive manner. The search was conduct on January 2022. A total of 10,832 studies were initially screened, and after applying the eligibility criteria, resulted in twenty studies. In general, the studies presented different methods of oral care and ways of using fluoride. Fluoride gel was the most applied fluoride method (70%). The results of this scoping review demonstrated that oral care such as hygiene instructions with regular dental follow-up and daily fluoride seem to be good strategies in preventing radiation-related caries.